2020
DOI: 10.3390/cells9112503
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein L10: From Function to Dysfunction

Abstract: Eukaryotic cytoplasmic ribosomes are highly structured macromolecular complexes made up of four different ribosomal RNAs (rRNAs) and 80 ribosomal proteins (RPs), which play a central role in the decoding of genetic code for the synthesis of new proteins. Over the past 25 years, studies on yeast and human models have made it possible to identify RPL10 (ribosomal protein L10 gene), which is a constituent of the large subunit of the ribosome, as an important player in the final stages of ribosome biogenesis and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Similarly, structural analysis of somatic cancer-associated RP mutations, including the mutation hotspots in RPL10 and RPS15 revealed that these RP mutations are localized in the regions associated with the catalytic core of ribosome, consistent with their influence on mRNA translation and thus global protein synthesis. 197,224 An altered translation pattern in cancer cells with RP mutations may promote oncogenic protein synthesis. For instance, the T-ALL-associated RPL10-R98S mutation protects leukemia cell survival via specific upregulation of IRES-dependent translation of the antiapoptotic molecule BCL2.…”
Section: The Molecular Basis Of Ribosomopathiesmentioning
confidence: 99%
“…Similarly, structural analysis of somatic cancer-associated RP mutations, including the mutation hotspots in RPL10 and RPS15 revealed that these RP mutations are localized in the regions associated with the catalytic core of ribosome, consistent with their influence on mRNA translation and thus global protein synthesis. 197,224 An altered translation pattern in cancer cells with RP mutations may promote oncogenic protein synthesis. For instance, the T-ALL-associated RPL10-R98S mutation protects leukemia cell survival via specific upregulation of IRES-dependent translation of the antiapoptotic molecule BCL2.…”
Section: The Molecular Basis Of Ribosomopathiesmentioning
confidence: 99%
“…Addition of the transcriptional inhibitor actinomycin D resulted in a loss of the typical nucleolar fluorescence, presumably caused by a stop of the production of pre-ribosomal particles. A pull-down experiment demonstrated that the labelled eIF6 was contained in molecular aggregates that comprised also the ribosomal protein Rpl10, an established component of pre-60S particles(reviewed by 42 ). Incubation with LMB, an inhibitor of pre-60S nuclear export by blocking Crm1, resulted accordingly in an increase of nuclear fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…In human, RPL10 is also known as the QM protein, which could be translocated from the cytoplasm to the nucleus promoted by presenilin 1 (PS1). The nuclear QM could bind to c-Jun protein as a negative regulator of the latter (Imafuku et al, 1999;Pollutri and Penzo, 2020). There are three paralogous genes encoding RPL10 in the Arabidopsis genome [RPL10A (At1G14320), RPL10B (AT1G26910), and RPL10C (AT1G66580)], with these genes sharing 90-95% sequence identity (Barakat et al, 2001).…”
Section: Extraribosomal Functions Of Rp Genes In Plants Free Rpl10a Involves In Transcriptional Regulations Of Certain Genesmentioning
confidence: 99%